Pentingnya Kedisiplinan di Sekolah Dasar Terutama di Kelas - Sukma Sharifah Andria; Ari Suriani (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
Education plays an important role in shaping the character and intelligence of the younger generation, with discipline as a key value that must be instilled from an early age, especially in elementary schools. Discipline not only maintains order during the teaching and learning process but also shapes students' personalities comprehensively. This study uses a descriptive qualitative approach through observation, interviews, and documentation to understand student discipline practices and the role of teachers in instilling this value in the classroom. The results show that discipline significantly contributes to students' academic success and is developed through consistent habituation. The teacher’s role as a behavioral model is crucial in fostering discipline awareness, with strategies involving students in rule-making as well as the implementation of educational rewards and punishments. Conversely, a lack of discipline causes disruptions in the learning process and lowers academic achievement. Therefore, sustainable discipline development involving multiple stakeholders is necessary to create an effective learning environment and strong student character